The effects of the combination of resistance exercise and heat stress on cell production and plasma levels of cytokines - Maryam Zilaei Bouri; Hamid Agha-Alinejad; Shirin Zilaei Bouri; Saeed Daneshmandi (Sport TK)
Global warming and its effects on human health encourage the examination of the effect of resistance exercise and heat stress on cytokines production. The aim of this study was to investigate the interaction effect of resistance training and heat on the immune system of healthy active men. Six trained males (27.83±1.9 years, 86.45±10.3 kg) completed a 60-minute resistance exercise with 75% 1RM in two conditions (~25 °C, normal or ~35 °C, heat). The following were evaluated: LPS-stimulated cytokine production, plasma cytokine levels, and cortisol. The results showed that heat stress increased (P=0.027) plasma IL-6 and remained high after 1 hr (P=0.026). Upon stimulation with LPS, IL-6 cell production in heat and normal conditions increased immediately (PH=0.026; PN=0.048), decreased 1 hr after exercise, and returned to baseline (PH=0.005; PN=0.033). However, post-exercise LPS-TNF-α release decreased immediately only in a heated environment (P=0.029). The concentration of blood cortisol was unaffected by normal or heat conditions. The findings of this research suggest that other factors beyond cortisol regulated cytokines during heat-exposed exercise. Furthermore, the IL-6 had a regulatory function on TNF-α release. These cytokine changes showed that real work in similar temperatures did not negatively affect the immune system.